Evaluasi Kualitas Air Limbah pada Sistem Pengolahan Air Limbah Domestik Terpusat (Spald-T) Kota Jambi - Virda Diah Agustina; Marhadi Marhadi; Peppy Herawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The problem of household waste has become so significant that it requires human resources to overcome it. To reduce pollution and recycle household waste, wastewater treatment facilities are needed. One of them is the International Paper Industry (IPAL) in Jambi City which uses APSDT (Antimicrobial photo-sonodynamic therapy) technology to treat domestic wastewater using moving bed biofilm reactor (MBBR) technology. To evaluate the quality of incoming and outgoing wastewater at the Jambi City IPAL, a study was conducted to measure pH (potential of Hydrogen), BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), TSS (Total Suspended Solid), Oil & Fat, Ammonia, and Total Coliform in accordance with Domestic Wastewater Quality Standards. Samples of the Jambi City IPAL were tested at the Jolli Lestari Internasional (JLI) Laboratory. The test results confirmed positive results for the TSS, Ammonia, and Total Coliform parameters, while the wastewater at the outlet also met the quality standards according to the Domestic Wastewater Quality Standards, except for the TSS parameter.